2015
DOI: 10.1007/978-3-319-20825-1_14
|View full text |Cite
|
Sign up to set email alerts
|

Endocannabinoids and the Cardiovascular System in Health and Disease

Abstract: The endocannabinoid system is widely distributed throughout the cardiovascular system. Endocannabinoids play a minimal role in the regulation of cardiovascular function in normal conditions, but are altered in most cardiovascular disorders. In shock, endocannabinoids released within blood mediate the associated hypotension through CB(1) activation. In hypertension, there is evidence for changes in the expression of CB(1), and CB(1) antagonism reduces blood pressure in obese hypertensive and diabetic patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 172 publications
(176 reference statements)
0
39
1
Order By: Relevance
“…Secondly, the effects of endocannabinoid release on cardioprotection was only observed in vitro, but not in in vivo study. However, considering the fact that cardiac endocannabinoid signaling in vivo could be influenced by cardiomyocytes, other cardiac cells, circulation, and neuroendocrine states [55, 56], the results that could gained in in vivo results might be different from the findings in our in vitro study. Nevertheless, the findings gained in our in vitro study identified the downstream signaling pathways in association with CB2R activation and cardioprotection of propofol conditioning that may foster further mechanistic studies.…”
Section: Discussioncontrasting
confidence: 61%
“…Secondly, the effects of endocannabinoid release on cardioprotection was only observed in vitro, but not in in vivo study. However, considering the fact that cardiac endocannabinoid signaling in vivo could be influenced by cardiomyocytes, other cardiac cells, circulation, and neuroendocrine states [55, 56], the results that could gained in in vivo results might be different from the findings in our in vitro study. Nevertheless, the findings gained in our in vitro study identified the downstream signaling pathways in association with CB2R activation and cardioprotection of propofol conditioning that may foster further mechanistic studies.…”
Section: Discussioncontrasting
confidence: 61%
“…Therefore, in various forms of hypertension, the eCB system becomes tonically active. This occurs by enhancing the vasorelaxant responses to eCBs, changes in plasma eCB concentration or alterations in the vascular expression of eCB system components, including up‐regulation of CB 1 receptors . It is worth mentioning that more research concerns the possible role of the eCB system in cardiovascular regulation in hypertension …”
Section: Introductionmentioning
confidence: 99%
“…N-Palmitoyl taurine*, 1-(1-enyl-stearoyl)-GPE, Palmitoylethanolamide*, N-Stearoyltaurine*, Oleoyl Ethanolamide*, 1-palmitoyl GPG, 10-Nonadecenoic acid, 15-Methylpalmitate), 4 are involved in the endocannabinoid (EC) Pathway. The EC system consists of cannabinoid receptors and their endogenous neuromodulatory lipid ligands that collectively play long-recognized roles in the neurological and immunological systems 29 and recently have been identified in the heart 30 . We found a roughly 50% decrease in the abundance of the biologically active EC metabolites oleoyl ethanolamide, palmitoyl ethanolamide, N-stearoyltaurine, and N-palmitoyltaurine after treatment with A61603 (Figure 2).…”
Section: Resultsmentioning
confidence: 99%